Inovasi Pembelajaran Matematika di Era Pandemi Covid-19 Pada Tingkat Sekolah Menengah Pertama - Jeanette Elisabeth Maro (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2022)
This thesis aims to describe research trends in mathematics learning innovation in the Covid-19 pandemic era for junior high school students and present implications and recommendations for mathematics learning innovations for junior high school students in the future. The method used in this writing is article review, which is done by browsing various articles from national and international journals. In the era of the Covid-19 pandemic, the learning process which is usually carried out in the classroom must be carried out at home via online (in the network) or remotely without meeting face to face. This makes it a challenge for educators to be able to innovate related to learning carried out in the pandemic era, especially in learning mathematics. The focus of this research is to describe research trends in mathematics learning innovation in the Covid-19 pandemic era. The methods used by researchers in data collection include questionnaires, observations, interviews, documentation and knowledge tests. Some studies use virtual classes, video conferencing and also use a combination of virtual classes and video conferencing in their learning. The recommendations for further research in order to use the right methods or media, which can answer problems that occur during online learning, so that learning can be effective, motivate and improve the results of mathematics learning so as to achieve its learning goals.